2007
DOI: 10.1080/07438140709353911
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Increases in Oxygen Depletion in the Bottom Waters of Boulder Basin, Lake Mead, Nevada-Arizona, USA

Abstract: Long-term changes in the hypolimnetic volumetric oxygen demand (HVOD) of Boulder Basin, Lake Mead were determined from dissolved oxygen profiles collected from 1991 to 2007. HVOD is the rate at which oxygen in a deep layer in contact with the sediments is depleted during the period of thermal and/or chemical stratification. Generally, the rate at which oxygen is depleted is correlated to the amount of organic debris in the hypolimnion and sediments. The sediment oxygen demand reflects historical organic loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…The relatively younger water at the lake surface compared to the older water at the lake bottom suggests that distinct vertical patterns exist in the lake's circulation processes. Additionally, it has been shown that in many years Boulder Basin does not completely destratify (LaBounty and Burns 2007). This vertical pattern could impact the lake's hydrodynamic process as well and may impact the distribution of the simulated water age.…”
Section: Impact Of Water Level Drawdownmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively younger water at the lake surface compared to the older water at the lake bottom suggests that distinct vertical patterns exist in the lake's circulation processes. Additionally, it has been shown that in many years Boulder Basin does not completely destratify (LaBounty and Burns 2007). This vertical pattern could impact the lake's hydrodynamic process as well and may impact the distribution of the simulated water age.…”
Section: Impact Of Water Level Drawdownmentioning
confidence: 99%
“…Moreover, numerical models can provide a useful method to analyze the impact of different water availability and management scenarios. Recent research on Lake Mead has primarily focused on field measurements and lab experiments (e.g., LaBounty andBurns 2007, Steinberg et al 2009). As for the present state of numerical models of Lake Mead, most have been conducted to predict hydrodynamic processes and water quality to understand past and present limnological conditions (SCOPEIS 2006).…”
mentioning
confidence: 99%
“…Lake Mead is mostly mesotrophic and monomictic (LaBounty and Burns 2005). LaBounty and Burns (2005Burns ( , 2007 defined three regions of Boulder Basin as the Inner, Middle, and Outer basins. The Inner Basin is characteristically more eutrophic, the Middle tends to be mesotrophic, while the Outer is meso-to oligotrophic.…”
mentioning
confidence: 99%
“…They found that higher concentrations of total phosphorus in Boulder Basin increased the hypolimnion oxygen depletion. With enhanced removal of phosphorous from wastewater entering Las Vegas Wash commencing in 2002, hypolimnion oxygen depletion rates in 2005 and 2006 were lower than previous years (LaBounty and Burns, 2007). This trend toward lower hypolimnion oxygen depletion rates from reduced nutrient input to Boulder Basin is likely responsible for the trend of increasing DO concentrations in the hypolimnion at Sentinel Island.…”
Section: Temporal-trend Analysesdeep-water Stationsmentioning
confidence: 93%
“…At other times, DO is well below saturation because of demand from bacteria breaking down organic matter. LaBounty and Burns (2007) found that hypolimnetic oxygen depletion was strongly positively associated with the amount of organic matter and nutrients entering Boulder Basin. They found that higher concentrations of total phosphorus in Boulder Basin increased the hypolimnion oxygen depletion.…”
Section: Temporal-trend Analysesdeep-water Stationsmentioning
confidence: 97%